Premature-nut-fall disease of coconut: a case study of Botryodiplodia theobromae and other fungi associated with the disease - EKHORUTOMWEN, OSAYOMORE ENDURANCE; CHIDI, NNAMDI IFECHUKWUDE; Shittu, Olalekan Hakeem (International Journal of Agricultural Sciences, 2023)
Coconut (Cocos nucifera L.) is grown in several countries, by millions of farmers globally. it provides a staple food and serves as a cash crop in many developing countries. Generally, about one third of the buttons produced in an inflorescence develop into mature nuts (that is, the number of buttons produced in a bunch often exceeds the number of nuts reaching maturity). Coconut production is affected by several factors among them diseases play a major role. The premature-nut-fall disease is a common problem encountered by coconut growers. The disease decreases the production potential of the coconut palm causing considerable yield loss. Hence, the study was carried out to investigate the incidence of the premature-nut-fall disease of coconut over two overlapping growing season in two major coconut growing areas. The Green dwarf (GD) coconut variety has a higher PDI of premature-nut-fall in both growing seasons and locations compared to other coconut varieties used in this study. The study also revealed that there is high variability in the PDI of premature-nut-fall across coconut varieties, sampling period in both growing seasons and locations. In both locations and growing seasons, the high percentage of fungi isolated from fallen nuts indicate the role of fungi pathogen in premature-nut-fall disease of coconut. Furthermore, isolation of B. theobromae from the internal tissues of diseased nuts, and other floral parts of coconut is an indication that the fungus is responsible for the premature-nut-fall disease of coconut resulting from fungi infection.